Antibacterial castor oil-based waterborne polyurethane/gelatin films for packaging of strawberries. (April 2023) - Zhong, Yuye; Zhang, Tao; Zhang, Wenshuo; Wang, Guannan; Zhang, Zhenhong; Zhao, Pingping; Liu, Xinghai; Li, Houbin
Abstract: Gelatin films for food packaging have gained popularity due to their affordability, strong renewability, and high biodegradability. However, pure gelatin film has poor stretch ability, moisture-sensitive, and no antibacterial properties, which limits its use in food industry. In this work, we effectively grafted quaternary ammonium groups onto a novel castor oil-based waterborne polyurethane (CWU). Gelatin was mixed with carious concentrations of CWU to create composite films. The mechanical properties, thermal stability, water permeability and oxygen permeability of these composite films improved dramatically with the increase of CWU concentration. The composite films demonstrated good inhibitory effect on Escherichia coli and Staphylococcus aureus due to the antibacterial capabilities of quaternary ammonium compound. The shelf life of the strawberry packaged in the composite film is extended to more than 6 days. Therefore, the new CWU mixed with gelatin could serve as an alternative food packaging material. Graphical Abstract: ga1 Highlights: Castor oil and quaternary ammonium salt were introduced into waterborne polyurethane. CWU was compounded with gelatin to obtain antibacterial packaging film WGL. Water resistance, mechanical properties and antibacterial activity were optimized. WGL film could effectively prolong the shelf life of strawberry.